An analysis of the environmental planning framework for coastal developments in Fiji's coral coast tourist region : a thesis presented in partial fulfilment of the requirements of a degree in Masters of Philosophy in Resource and Environmental Planning at Massey University - Tuvuki, Suliasi Wavu (Massey University, 1995)
This thesis examines Fiji's environmental planning framework with particular reference to tourism development along the coast. This focus is an acknowledgement of the coastal ecosystems upon which the tourism industry depends. However, despite this emphasis, the findings in this thesis could be relevant to all types of development in Fiji. Firstly, the shortcomings of the present planning framework are identified, with particular attention being paid to the sectoral nature of the existing institutional and legal arrangements. The important role of EIA is also discussed and is applied to the situation in Fiji's. Particular attention is placed upon the way the present system does not sufficiently recognise the important role the indigenous Fijian plays in the development planning process. This seems unjust since the indigenous rural dweller is the most affected by tourism developments along the coast and so the case study area, Korolevu, was chosen to provide a typical example of how such large scale, unsustainable, coastal developments have in the past, because of flaws in the present system, were often established with little appreciation for the traditions, protocols and more sustainable environmental management practices of the traditional local people. Now that the international community is beginning to recognise the importance of providing sustainable development which preserves the environment in the fullest sense, including the cultural environment into which development is placed, the Government of Fiji is starting to recognise the importance of applying such strategies as Caring for the Earth (IUCN/UNEP/WWF 1991) and Agenda 21 (Sitarz 1993) to the situation in Fiji. The findings of this thesis result in various reforms which have the achievement of sustainable development practices in the Fijian cultural context as the underlying focus. These reforms emphasise the need to recognise and implement indigenous rights into the environmental planning framework at policy, institutional and legal levels. The incorporation of the indigenous Fijian's interests in this framework is an essential component to providing sustainable practices in Fiji. This inclusion can only be achieved by providing meaningful public participation opportunities for such communities. Ultimately, the IUCN/UNEP/WWF (1991) and Sitarz (1993) documents and, in addition, New Zealand's Resource Management Act (1992) collectively provide a useful model out of which the Fiji Government could develop its own environmental management regime which promotes sustainable development through the identification, avoidance, mitigation and remedying of the many environmental problems encountered in Fiji's coastal environment.
Keywords: Fiji; Coastal zone management; Environmental policy